Multivariate Analysis of Some Clinical Parameters by Gender and Age in Patients with COPD for the First Time Diagnosed - AKDUMAN, Seha; SAHİP, Yusuf (International Journal of Innovative Research in Medical Science, 2019)
Aim: In this study, it was aimed to analyze the different clinical parameters according to gender and age for the first time in patients diagnosed with COPD. Methods: The study was designed retrospectively. Patients who were admitted to Kadikoy Medicana Hospital between 12.10.2017 and 12.10.2018 with respiratory complaints and COPD diagnosed for the first time were included in the study. A total of 160 patients with the diagnosis of COPD for the first time among 845 patients were included in the study. Age, gender, urea, creatinine, CRP, NEU, WBC, EOS and HGB values were obtained from the patient files. Findings: Clinical parameters of CRP, urea, creatinine, WBC, NEU and HGB were higher in male patients and EOS was higher in female patients. According to the results of the difference analysis, only HGB levels were statistically different between the groups (p <0.05). According to uncontrolled gender correlation analysis in patients with COPD for the first time, CRP (r = 0.224; p <0.01), urea (r = 0.580; p <0.01), creatinine (r = 0.331; p <0.01), creatinine (r = 0.331; p <0.01), EOS (r = -0.172; p<0.05) and HGB (r = -0.319; p <0.01) level correlations with age were statistically significant. There was a positive correlation between CRP, urea and creatinine and age, and there was a negative correlation between EOS and HGB and age. Age and urea (r = 0.573; p <0.01) and creatinine (r = 0.426; p <0.01) were statistically significant and positively correlated in women with firstly diagnosed COPD. Correlations between age and other research parameters were not statistically significant (p> 0.05). CRP (r = 0.300; p <0.01), urea (r = 0.565; p <0.01), creatinine (r = 295; p <0.05), creatinine (r = 295; p <0.05), EOS (r = -0.225; p <0.05) and HGB (r = -0.372; p <0.01) were significantly correlated in male patients who firstly diagnosed with COPD. The direction of the correlation was positive for CRP, urea and creatinine, and negative for EOS and HGB parameters. Conclusion: The results of the study show that age and urea and creatinine levels of the women with COPD diagnosis for the first time have changed according to age. In males, CRP, urea, creatinine, EOS and HGB values change according to age. Therefore, it is useful to study gender and age-related mechanisms in COPD.